Pediatric emergency in Brazil: the consolidation of an area in the pediatric field - Jefferson P. Piva; Patrícia M. Lago; Pedro Celiny R. Garcia (Elsevier, 2017)
Objective: The aim of this study was to present a review on the evolution, development, and consolidation of the pediatric emergency abroad and in Brazil, as well as to discuss the residency program in this key area for pediatricians. Data sources: This was a narrative review, in which the authors used pre-selected documents utilized as the minimum requirements for the Residency Program in Pediatric Emergency Medicine and articles selected by interest for the theme development, at the SciELO and Medline databases, between 2000 and 2017. Data synthesis: The historical antecedents and the initial evolution of pediatric emergency in Brazil, as well as several challenges were described, regarding the organization, the size, the training of professionals, and also the regulation of the professional practice in this new specialty. Additionally, a new pediatric emergency residency program to be implemented in Brazil is described. Conclusions: Pediatric emergency training will be a powerful stimulus to attract talented individuals, to establish them in this key area of medicine, where they can exercise their leadership by promoting care qualification, research, and teaching, as well as acting decisively in their management. Resumo: Objetivo: O estudo teve como objetivo apresentar uma revisão sobre a evolução, desenvolvimento e consolidação da Emergência Pediátrica no exterior e no Brasil assim como discutir o programa de residência nesta importante área de atuação para o pediatra. Fontes dos dados: Trata-se de uma revisão do tipo narrativa, em que os autores utilizaram documentos pré-selecionados empregados nos requisitos mínimos para o programa em Residência de Medicina de Emergência Pediátrica e artigos selecionando por interesse para desenvolvimento do tema utilizaram as bases de dados SciELO e Medline entre 2000 e 2017. Síntese dos dados: Foram descritos os antecedentes históricos e a evolução inicial da Emergência Pediátrica no Brasil e diversos desafios, na organização, no dimensionamento, na formação de profissionais e, também, na regulamentação do exercício profissional desta nova especialidade. Também se descreve um novo programa de residência em Emergência Pediátrica a ser implementado no Brasil. Conclusões: A formação em emergência pediátrica será um poderoso estímulo para atrair indivíduos talentosos, fixá-los nesta importante área da medicina, onde poderão exercer sua liderança promovendo qualificação na assistência, na pesquisa e no ensino, assim como atuando decisivamente no seu gerenciamento. Keywords: Emergency, Pediatrics, Medical residency, Teaching program, Palavras-chave: Emergência, Pediatria, Residência médica, Programa de ensino